194k views
2 votes
Simplify 3 divided by 5-6i

2 Answers

2 votes

Answer:


(15)/(61)+(18)/(61)i

Explanation:


(3)/(5-6i)

To simplify or to write in the form a+bi, you will need multiply the top and bottom by the bottom's conjugate like so:


(3)/(5-6i) \cdot (5+6i)/(5+6i)

Keep in mind when multiplying conjugates you only have to multiply first and last.

That is the product of (a+b) and (a-b) is (a+b)(a-b)=a^2-b^2.

(a+b) and (a-b) are conjugates

Let's multiply now:


(3)/(5-6i) \cdot (5+6i)/(5+6i)=(3(5+6i))/(25-36i^2)

i^2=-1


(15+18i)/(25-36(-1))


(15+18i)/(25+36)


(15+18i)/(61)


(15)/(61)+(18)/(61)i

4 votes

For this case we must simplify the following expression:


\frac {3} {5-6i}

We multiply by:


\frac {5 + 6i} {5 + 6i}\\\frac {3} {5-6i} * \frac {5 + 6i} {5 + 6i} =\\\frac {3 (5 + 6i)} {(5-6i) (5 + 6i)} =\\\frac {3 (5 + 6i)} {5 * 5 + 5 * 6i-6i * 5- (6i) ^ 2} =\\\frac {3 (5 + 6i)} {25-36i ^ 2} =\\\frac {3 (5 + 6i)} {25-36 (-1)} =\\\frac {3 (5 + 6i)} {25 + 36} =\\\frac {3 (5 + 6i)} {61} =\\\frac {15 + 18i} {61}

Answer:


\frac {15 + 18i} {61}

User Steve Cook
by
4.8k points